2021
DOI: 10.1186/s13256-021-02896-1
|View full text |Cite
|
Sign up to set email alerts
|

Erysipelas of the right arm due to Bordetella trematum: a case report

Abstract: Background Bordetella trematum is unknown to most clinicians and microbiologists. However, this Gram-negative opportunistic bacterium can be responsible for ulcer superinfection but also bacteremia and sometimes death by septic shock. Case report We report the case of erysipelas due to B. trematum with bacteremia in an immunocompromised 88-year-old Caucasian patient. Conclusion In immunocompromised pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…The virulence string and clonal lineage of the other HLGR-GBS serotypes identified in this study are in line with findings from previous studies, confirming the already observed specific association between serotype, pili, alpha-like proteins, and clonal complexes [41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 92%
“…The virulence string and clonal lineage of the other HLGR-GBS serotypes identified in this study are in line with findings from previous studies, confirming the already observed specific association between serotype, pili, alpha-like proteins, and clonal complexes [41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 92%
“…Two cases of bacteraemia reported by Majewski et al [12] and Lacasse et al [13] had originated from infected skin and soft tissue sites, but resulted in very different clinical outcomes. Majewski et al described a fatal case from a rapidly progressive deep tissue Since 2015, there has been a cumulative number of B. trematum bacteraemia cases reported (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…[12] and Lacasse et al . [13] had originated from infected skin and soft tissue sites, but resulted in very different clinical outcomes. Majewski et al .…”
Section: Discussionmentioning
confidence: 99%
“…B. trematum has been previously delineated as a unique bacterial species after a polyphasic investigation of ten isolates, including six isolates recovered from open wounds in patients, most of whom were European in origin [31]. B. trematum was further isolated in thirteen patients presenting with chronic cutaneous ulcers sometimes extending to underlying tissues and bones, and most patients originated from European countries [32][33][34][35][36][37], the United States [38], Brazil [39], Argentina [40] and Japan [41]. However, B. trematum has never been previously reported as a co-pathogen with M. ulcerans.…”
Section: Discussionmentioning
confidence: 99%